Perlindungan Hukum terhadap Tenaga Kerja Indonesia yang Bekerja di Luar Negeri Berdasarkan Prinsip Negara Hukum - Shaviera Indar Dhanty; Parasian Simanungkalit; Dadang Herli Saputra (Syntax Literate, 2023)
The low level of education of migrant workers working abroad often makes the fate of migrant workers less favorable. Although this is not entirely true, those affected by the calamity of injustice treatment that are detrimental to most of those with less education. The level of education will also greatly affect language acquisition, access to technological information and the culture in which they work, especially for migrant workers who work in institutions or institutions, such as hospitals, restaurants, shops, and other institutions that make language as a means of communication is a very crucial issue. This means the quality of education is an important factor in consideration in sending workers abroad. The meaning and significance of work for everyone is reflected in the 1945 Constitution Article 27 paragraph (2) states that every Indonesian citizen has the right to work and a decent living for humanity. The migrant worker placement program abroad is one of the efforts to overcome the unemployment problem. The role of the government in this program focuses on aspects of development, protection and providing various facilities to related parties, especially migrant workers and Private Indonesian Labor Placement Implementers (PPTKIS). If you have obtained permission from the government to carry out migrant worker placement services abroad in accordance with Law No. 39 of 2004 concerning the Placement and Protection of Indonesian Workers Abroad. In terms of protection for migrant workers, the right to protection starts from pre-placement, placement period, until post-placement.